Riding the Blue Wave : Applying the Blue Economy Approach to World Bank Operations - World Bank (World Bank, Washington, DC, 2022)
In close collaboration with international institutions, development partners, and client countries, the World Bank is leading the effort to develop and operationalize the concept of the blue economy by focusing on the integration and sustainability of different oceanic sectors. The aim is to limit their impacts on ocean health, taking into account the additional risks posed by climate change. The blue economy approach to ocean development therefore aligns well with the World Bank’s twin goals of reducing extreme poverty and enhancing shared prosperity. The main objective of this document is to provide guidance on how to apply a blue economy lens to Bank operations. To this end, it aims to: ensure that the World Bank’s operations around oceanic activities are developed with a view to improving the necessary integration between different economic sectors, both on land and at sea, and avoiding unnecessary impacts on ocean health; and identify means to scale up blue economy activities, including through new sources of innovative blue finance. To achieve these goals, two related streams of work are identified: one focused on promoting an integrated approach to the sustainable development of oceanic sectors, and the other focused on increasing blue financing.